The Influence of Performance Allowances on Employee Work Performance at the Makassar State Administrative Court - Suprianto Suprianto; Rezki Suci; Jamaluddin Jamaluddin (International Journal of Administration and Education (IJAE), 2024)
The government, in supporting the improvement of work quality and employee welfare, has issued one policy, namely providing performance allowances to civil servants. Employees play a very active role in every organizational activity because employees determine the realization of organizational goals. Therefore, providing performance allowances is expected to be able to motivate employees to produce good work results or work performance. This research aims to determine the description of performance allowances, work performance, and the magnitude of the influence of performance allowances on the work performance of employees of the Makassar State Administrative Court. This research is quantitative research with a correlational type of research. The sample in this study was 32 people using simple random sampling techniques. The data collection techniques used were questionnaires, interviews, and documentation. Meanwhile, the data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The test results show that the performance allowance variable is in the very high category, while the work performance variable is in the very good category. Based on the results of the product-moment correlation test, the relationship between variables is moderate and there is a positive and significant influence of performance allowances on the work performance of Makassar State Administrative Court employees of 27.4%. The research results show that with performance benefits employees are more disciplined and enthusiastic in improving their work performance.